The effect of teaching using multimedia on mathematical anxiety and motivation - Yaftian, Narges; Barghamadi, Saeid (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2022)
In Iran and many other parts of the world, teaching and learning mathematics has confronted students and teachers with many challenges such as lack of motivation and increased anxiety. Thus, the current situation should be changed and shifted to active methods. One of the active methods is teaching with the help of multimedia. The purpose of this study was to investigate the effect of teaching using multimedia systems on the students' motivation and anxiety in mathematics. The method is a quasi-experimental with pretest and posttest design with a control group. Based on the available sampling, two classes were selected and a class was randomly assigned to the experimental group and the other to the control group. The tools were questionnaires on mathematical anxiety and motivation. In 8 sessions, using multimedia systems, the experimental group was taught, but in the control group, the same concepts were taught in a conventional way in Iran. In the end, Mathematical Anxiety and Mathematical Motivation Questionnaires were performed on both groups. The results showed that there was a significant difference between the two groups in each of the dependent variables and the use of multimedia systems has affected the students’ motivation and anxiety in mathematics.